2011
DOI: 10.4999/uhod.09164
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Converting Enzyme Insertion/Deletion Gene Polymorphisms in Leukemic Hematopoiesis

Abstract: Local bone marrow renin-angiotensin system (RAS) is an autocrine-paracrine system affecting normal and neoplastic hematopoiesis. Angiotensin converting enzyme (ACE) converts angiotensinogen-I to its physiologically active peptide angiotensin-II, which stimulates proliferation and differentiation of hematopoietic stem cells through angiotensin II type 1 receptors. We investigated the ACE insertion/deletion (I/D) gene polymorphisms in patients with hematological malignancies including acute and chronic leukemia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
2
9
1
Order By: Relevance
“…7,8 There is preliminary evidence that local BM RAS could affect neoplastic hematopoiesis. [9][10][11][12][13][14][15][16] Over-expression of the angiotensin-converting enzyme (ACE) (CD 143) surface antigen in leukemic myeloid blast cells have been detected by flow cytometric analyses. Moreover, a positive correlation has been found between the ACE and BM blast count.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 There is preliminary evidence that local BM RAS could affect neoplastic hematopoiesis. [9][10][11][12][13][14][15][16] Over-expression of the angiotensin-converting enzyme (ACE) (CD 143) surface antigen in leukemic myeloid blast cells have been detected by flow cytometric analyses. Moreover, a positive correlation has been found between the ACE and BM blast count.…”
Section: Introductionmentioning
confidence: 99%
“…We investigated ACE I/D gene polymorphisms in patients with haematological malignancies, including acute and chronic leukaemia, myelodysplastic syndrome and multiple myeloma. Our results showed that 80.4 % of the patients had a ID/II genotype compared with 55.9 % in the control group, with a 3.2-fold increased disease risk in the presence of the insertion allele (ID/II) [122].…”
Section: Acementioning
confidence: 58%
“…Moreover, a positive correlation has been found between ACE and BM blast count. 17 Hence, local BM RAS has been investigated in acute leukaemias 17,18,44,[46][47][48][49] and chronic myeloproliferative disorders, 32,43,[50][51][52][53] and angiotensin has been suggested to act as an autocrine growth factor for AML cells. We investigated the ACE insertion/ deletion (I/D) gene polymorphisms in patients with haematological malignancies including acute and chronic leukaemia, myelodysplastic syndrome and multiple myeloma.…”
Section: Local Haematopoietic Bone Marrow Renin-angiotensin System In Neoplastic Haematopoiesismentioning
confidence: 99%
“…Our results showed that 80.4% of the patients represented the ID/II genotype, compared with 55.9% in the control group, demonstrating a 3.2-fold increased disease risk for the insertion allele (ID/II). 49 Consequently, increased production of AngII by membranebound ACE could result in leukaemic transformation of BM haematopoietic cells by co-ordinated activation of signal transduction pathways via the AT-1 receptor and/or receptor transactivation. 54 Immunohistochemical studies have shown the possible role of ACE/RAS in BM by evaluating ACE expression in normal BM, several myeloproliferative disorders and myelodysplasia.…”
Section: Local Haematopoietic Bone Marrow Renin-angiotensin System In Neoplastic Haematopoiesismentioning
confidence: 99%